Making race : the politics and economics of coloured identity in South Africa - Goldin, I (Maskew Miller Longman, 1987)
At the heart of the revised constitution recently imposed on South Africa lies an attempt to reconstitute Coloured political identity. The constitutional changes have fuelled an intense ideological and political conflict over the subject of Coloured identity. This passionate debate cannot be separated from the wider struggle being waged against the South African regime. Indeed, therein lies its particular historical significance...